Berberine-containing natural-medicine with boiled peanut-OIT induces sustained peanut-tolerance associated with distinct microbiota signature - Srivastava, Kamal; Cao, Mingzhuo; Fidan, Ozkan; Shi, Yanmei; Yang, Nan; Nowak-Wegrzyn, Anna; Miao, Mingsan; Zhan, Jixun; Sampson, Hugh A.; Li, Xiu-Min (Frontiers in Immunology, 2023)
Background: Gut microbiota influence food allergy. We showed that the natural compound berberine reduces IgE and others reported that BBR alters gut microbiota implying a potential role for microbiota changes in BBR function. Objective: We sought to evaluate an oral Berberine-containing natural-medicine with a boiled peanut oral immunotherapy (BNP) regimen as treatment for food allergy using a murine model and to explore the correlation of treatment-induced changes in gut microbiota with therapeutic outcomes. Methods: Peanut allergic (PA) mice, orally sensitized with roasted peanut and cholera toxin received oral BNP or control treatments. PA mice received periodic post-therapy roasted peanut exposures. Anaphylaxis was assessed by visualization of symptoms and measurement of body temperature. Histamine and serum peanut-specific IgE levels were measured by ELISA. Splenic IgE+B cells were assessed by flow cytometry. Fecal pellets were used for sequencing of bacterial 16S rDNA by Illumina MiSeq. Sequencing data were analyzed using built-in analysis platforms. Results: BNP treatment regimen induced long-term tolerance to peanut accompanied by profound and sustained reduction of IgE, Symptom scores, plasma histamine, body temperatures and number of IgE+ B cells (p <0.001 vs Sham for all). Significant differences were observed for Firmicutes/Bacteroidetes ratio across treatment groups. Bacterial genera positively correlated with post-challenge histamine and PN-IgE included Lachnospiraceae, Ruminococcaceae and Hydrogenanaerobacterium (all Firmicutes) while Verrucromicrobiacea. Caproiciproducens, Enterobacteriaceae and Bacteroidales were negatively correlated. Conclusions: BNP is a promising regimen for food allergy treatment and its benefits in a murine model are associated with a distinct microbiota signature.